Gastric and small intestinal lesions after partial stomach resection with Billroth II or Roux-en-Y reconstruction in the rat - Kobayasi, Shoiti [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Camargo, João Lauro Viana de [UNESP]; Imai, Toshio; Yuasa, Hirofumi; Ogawa, Kumiko; Tatematsu, Masae (Elsevier B. V., 1994)
The evolution and phenotypic expression of mucosal lesions of the gastric stump were investigated in male rats submitted to gastric resection with reconstruction by the Billroth II technique (BII with biliopancreatic reflux, BPR) or by the Roux-en-Y procedure (without BPR). Animals were studied at 24, 36, 54 and 64 weeks after surgery and the phenotypic expression of lesions analysed using routine hematoxylin and eosin staining, immunohistochemical staining for pepsinogen isoenzyme 1 and histochemical procedures for mucins (paradoxical concanavalin A, galactose oxidase Schiff (GOS) and sialidase GOS reactions). BPR was found to be responsible for the formation of adenomatous hyperplasia (AH), increasing in incidence and size with time, since the Roux-en-Y procedure failed to induce the gastric stump lesions observed after BII reconstruction. AHs always occurred in the transition of the gastrojejunal junction, a site offering special conditions for BPR influence, and were classified as gastric (G), intestinal (I) and G+I types according to their phenotypic expression. No pure I type AH was diagnosed at any time point. The G and G+I types developed at approximately equal incidences (i.e., G type 7/17, G+I type 10/17 at the 64th week). It was suggested that both gastric and intestinal mucosal elements were stimulated to proliferate by BPR, with the gastric mucosa tending to demonstrate AH. Intestinal type components of AH were found adjacent to the jejunum and not at the stomach margin, indicating an origin from intestinal mucosa. No metaplasia of the gastric mucosa was observed in any animal after partial gastric resection. In 101 rats submitted to the BII procedure, 5 mucinous adenocarcinomas were eventually diagnosed, mostly located in the subserosa of the gastrojejunal junction. All carcinomas expressed the phenotype of cells of the small intestine. Evidence of malignant transformation within the gastric components of AH was not observed even at the 64th week. In conclusion, all lesions induced by BPR in the rat remnant stomach are benign, and the few true cancers that arise in association are derived from the small intestine.
Keywords: Rat; Biliopancreatic retlux; Gastric mucosa; Hyperplasia; Cancer; Phenotype